Correlation between histopathological and endoscopic findings in upper gastrointestinal biopsies of dyspeptic patients: A cross-sectional study - Nepal, Niraj; Shrestha, Oshan; Choudhary, Prabesh; Priya, Khushboo (Journal of Pathology of Nepal, 2025)
Background: Dyspepsia is a common clinical problem with a wide differential diagnosis, and the patterns of upper gastrointestinal mucosal disease vary across regions. Correlating endoscopic impressions with histopathological findings is essential for accurate diagnosis, particularly in settings where Helicobacter pylori infection remains prevalent. The study aimed to evaluate the spectrum of upper gastrointestinal mucosal lesions in dyspeptic patients and determine the correlation between endoscopic and histopathological diagnoses.Materials and Methods: This cross-sectional observational study included 358 adult dyspeptic patients who underwent upper gastrointestinal endoscopy with targeted mucosal biopsies at Nobel Medical College, Nepal. Endoscopic impressions were compared with corresponding histopathological findings, and Helicobacter pylori positivity was assessed using routine and special stains.Results: The mean patient age was 44.9 ± 14.5 years, with a peak in the fourth decade; males comprised 58.9%. Erythematous or nodular gastritis was the most common endoscopic finding (50.3%). Histology showed chronic non-specific gastritis as the predominant lesion (33.0%), followed by gastric ulcer (15.1%) and chronic active gastritis (14.5%). H. pylori was prevalent in 40.8%, with the highest rates in chronic active gastritis (90.4%) and gastric ulcer (64.8%). Concordance between endoscopic and histopathologic findings was excellent for gastric and duodenal ulcers as well as malignant lesions, all endoscopically suspected malignancies were confirmed on biopsy.Conclusions: Most dyspeptic patients had benign inflammatory pathology, and combining endoscopy with histopathology significantly improved diagnostic accuracy. Helicobacter pylori infection remained strongly associated with active gastritis and ulcer disease. Endoscopic biopsy continues to play a central role in evaluating dyspepsia in regional clinical practice.